Determination of phthalate esters in Egyptian PET-bottled water investigated under different storage conditions - Zaki, Ghada Ismail (AUC Knowledge Fountain, 2015)
Phthalate esters are organic compounds that are extensively used in polymers manufacturing and many commercial products and can induce serious adverse health effects upon human exposure. The migration of phthalates esters from PET plastic bottles into water especially under poor storage conditions is subject to scientific debate. This study is the first to assess the occurrence of six phthalates in different branded PET bottled water locally produced in the Egyptian market. The samples were analyzed using liquid-liquid extraction with dichloromethane and GC/MS under various storage conditions. Among the six analyzed phthalates, three were detected at sub ppb levels where DEHP was the dominant phthalate followed by DBP. The data suggests that time and temperature correlate with the increase of phthalates migration. The levels of phthalates detected in all samples were significantly below the maximum contaminant limits established by the FDA and the EPA. Throughout the study, the concentration range of DEHP varied from <0.062 µg l-1 and reached a maximum concentration of 0.617 µg l-1, while for DBP the concentration ranged from <0.043 µg l-1 to a maximum concentration of 0.549 µg l-1. DEP was also detected but in very small concentration values, such that the highest recorded concentration for DEP over the whole study was 0.062 µg l-1. The estimated daily intakes to phthalates via bottled water were calculated from the measured phthalates concentrations and were reported to be considerably lower than their respective tolerable daily intake values established by EFSA. The contribution of water to phthalates daily intakes did not exceed 0.16% and 0.72 % of the TDI values for DBP while these values were 0.04% and 0.16% for DEHP in adults and toddlers, respectively